Ethnobotanical investigation on medicinal plants in the Vesuvio National Park (Campania, Southern Italy). (4th November 2016) - Menale, Bruno; De Castro, Olga; Cascone, Ciro; Muoio, Rosa
Abstract: Ethnopharmacological relevance: This paper illustrates the results of an ethnobotanical study carried out in the Vesuvio National Park (VNP) (Campania, Southern Italy). It describes the medicinal uses of the plants in an ancient area rich in ethnobiodiversity investigated for the first time. Aim for the study: The main aim of the study was to understand at what extent current knowledge on medicinal plant uses is still alive in VNP. Materials and methods: The informations were collected using semi-structured and unstructured interviews performed on 136 persons living in the investigated area from March to November 2014 and from April to October 2015. The age of the informants ranged from 47 to 85 years old; more than half of the informants aged between 61 and 70. Local plant uses were listed and analyzed in a table and compared with uses in other localities in Italy and in other regions of the Mediterranean basin. Results: In VNP were recorded a total number of 132 plant species, belonging to 110 genera and 51 families mentioned for medicinal purposes. Among the recorded 132 plant species, 70 are spontaneous or subspontaneous and 62 are cultivated above all in the kitchen gardens or in the apartments, as food or as ornamental. Herbs represent the majority, followed by trees and shrubs or subshrubs. The investigated plants were used to cure 116 different human health diseases and 4 veterinary problems. The majority of plants are used in the treatment of gastrointestinal, skin and respiratory problems. Conclusion: The number of medicinal plants reported in this paper reflects a well-preserved traditional popular knowledge (TPK) of the elderly people living in the rural areas and in the small villages of VNP. The conservation of TPK is owed to the persistence of an oral tradition that safeguard the use of plants as herbal medicine. We realized that while the use of some wild plants is decreasing, people continue to gather some cultivated and invasive plants for preparing remedies. Researches like this are necessary to protect ancient memories, to promote the transfer of information to the younger generations, to preserve ethno-biodiversity and to provide a starting point fur further biochemical investigations on medicinal entities. Graphical abstract: